The German Retirement Benefit Formula: Drawbacks and Alternatives - Mathias Kifmann; Friedrich Breyer (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
In this paper we identify a number of objectionable features of the German retirement benefit formula. We show that groups of insureds with higher than average life expectancy, in particular high-income groups, are subsidized by the rest of the membership because the formula neglects differences in group-specific life expectancy. Furthermore, the current formula leads to undesirable long-run effects if the earnings ceilings is raised, mandatory membership is extended, life expectancy rises or the rate of population growth declines. We present two alternative formulas which take group-specific life expectancy into account. In particular, a return-rate formula which rewards each Euro of contributions with the internal rate of return of the pay-as-you-go pension system proves to be superior to the current formula – – Wir diskutieren eine Reihe von Problemen der Rentenformel in der deutschen gesetzlichen Rentenversicherung (GRV). Wir zeigen, dass Bevölkerungsgruppen mit überdurchschnittlicher Lebenserwartung, insbesondere die besser Verdienenden, von den übrigen Versicherten subventioniert werden, da die Rentenformel Unterschiede in den gruppenspezifischen Lebenserwartungen nicht berücksichtigt. Außerdem führt die Formel zu unerwünschten langfristigen Wirkungen, wenn die Beitragsbemessungsgrenze erhöht oder die Pflichtmitgliedschaft ausgeweitet wird, wenn die Lebenserwartung steigt oder das Bevölkerungswachstum abnimmt. Wir schlagen zwei Alternativen vor, die die gruppenspezifische Lebenserwartung berücksichtigen. Wir zeigen, dass insbesondere die Interne-Rendite-Formel, die jeden Euro an Beiträgen mit der internen Rendite des Umlageverfahrens belohnt, gegenüber der gegenwärtigen Formel überlegen ist
Keywords: H22; J18; H55; 330; Rentenversicherung; implizite Besteuerung; intra- und intergenerative Gerechtigkeit; pay-as-you-go pension systems; implicit taxation; intra- and intergenerational equity; Gesetzliche Rentenversicherung; Versicherungstechnik; Verteilungswirkung; Generationenbeziehungen; Gerechtigkeit; Deutschland; Rentenformel